INVESTMENT PROCESS: EMPOWERING STATE POLICY - A. Medved’ (Вестник университета)
The problem of stimulating state policy in relation to the investment process is investigated in the paper. Arguments in favor of active institutionalization of investment process are presented. Favorable or hindering conditions for investment process are systematized. The situation in the Russian Federation relating to the development of the institutions needed for the progressive process of the investing is analyzed. The classification of investments in accordance with the objectives of investors is presented. The measures for state support of strategic investments is suggested.